The Sooner, the Worse? Association between Earlier Age of Sexual Initiation and Worse Adolescent Health and Well-being Outcomes - Osorio, Alfonso; Lopez-del Burgo, Cristina; Carlos, Silvia; de Irala, Jokin (Frontiers in Psychology, 2017)
This cross-sectional study assesses the association between age of sexual initiation during adolescence and a selection of well-being outcomes regarding that first relationship. High-school adolescents from El Salvador (2,686) and from Peru (3,399) replied to a paper-pencil questionnaire. Those who were sexually initiated replied to several questions regarding their age at sexual initiation, condom use, satisfaction and reasons/circumstances for that sexual relationship. Approximately 19% of participants were sexually initiated (n=1,179). After retaining participants with valid responses and with sexual initiation ages between 13 and 17, the final sample for this paper consisted of 996 sexually initiated participants (526 Salvadorians and 470 Peruvians). Multiple logistic regression analyses showed that those who initiated sex at earlier ages had worse outcomes compared to those who initiated at older ages. Specifically, they had lower odds of having used a condom, of having good memories of that experience and of having had that first relationship because they were in love. Conversely, they had higher odds of having had that first sexual relationship as a result of peer pressure (“Most of my friends already had sex”), because of partner pressure (“I was afraid to lose him/her”, “My partner told me he/she would leave me” or “I did not know how to say no to a person who insisted”), or as a consequence of different forms of impaired autonomy (“I was under the influence of alcohol or drugs” or “As a consequence of seeing sexual images”). Results show that sex at earlier ages is associated with worse adolescent health and well-being outcomes.